Tanggung Jawab Pelaku Usaha Transportasi Laut Terhadap Penumpang di Provinsi Kepulauan Riau - Muhammad Fajar Hidayat (Jurnal Selat, 2015)
The 95 % of Riau Archipelago Province’s territorial is an ocean and only 5% is land which gives an oportunity for businessman to provide sea transportation service, it is started from ferry which connect regency or cities in a far distance, Pompong ship which connect an island with another island in a short distance , and roro ship (roll on roll off) which is used by society to carry their vehicles to the outside area. Particially we still find a passenger (costumer) who are unprofitable with the sea transportation business such as overload passenger the lost or broken luggaeges which is put on the deck, the delayed schedule ship without notification to the passengers, and the scrratch of the passenger’s vehicles when they entered into the ship. The problems of this research is how the responsibility of sea transportation business to the passangers in Riau Archipelago Province, the author of this resaerch uses a normative legal of methodology the result which is found by the author of this research are, first if the businessman load the passengers over than capacity so that there will be a passenger who does not get any seat then, the businessman will get an absolute responsibility principle (absolute liability), second, if the passenger’s luggaes are lost or broken when they are put on the ship’s deck, then the businessman will get a punishment from the government based on their faults (the fault of liability or liability based on fault), third, if the passengers get a delay schedule ship without notification about it, then, the sea transportation businessman will be punished by presumption of liability principle, and, forth if the passanger’s vehicles scracthed when they enter into the roll on roll off ship which is cause by the ship crew while instructing the passenger to park their vehicles and arranging those vehicles, then the sea transportation businessman will punished by strict liability. Key words : Responsibility, Producent, Consume